The Triple System for Regulating Women's Reproduction. Issue 2 (June 2015) - Carbone, June; Cahn, Naomi
<x xml:space="preserve">Abstract</x> Analysis of ART and abortion must include the experiences of women at the emerging center of American life, as well as those at the top and bottom of the socioeconomic scale. Our contribution explores the triple system of fertility regulation, analyzing the intersections between fertility and class and using the experiences of women in the middle to add depth to our understanding of women's exercises of autonomy.